Harmonic current effect on the sizing of neutral conductor of low voltage distribution network - Azharudin Mukhtaruddin (School of Electrical Systems Engineering, Universiti Malaysia Perlis, 2015)
Power system harmonic phenomenon was an old problem, but with renewed and unprecedented threat. This matter deserved to get a refreshing look as proliferation of non-linear loads, one of the harmonic sources, has been increasing exponentially especially at low voltage network. Despite this fact, research into the problem seemed to be declining.